SPESIES IKAN YANG DITEMUKAN DI SUNGAI KENAGARIAN AUR BEGALUNG KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Marta, Prezi - (Pendidikan Biologi, 2014)
The river of Kenagarian aur Begalung district of Bayang was a river running along the residential areas. The river Kenagarian aur Begalung was the role as a backup source of water, prevent occurrence of water. The surrounding community also used the river as a Quarry of Stone, Quarry of sand, and catching of fish. The catching of fish conducted by community using of stun and poison of fish, so that these activities would resulted discription of existing organisms in the river. Not just fish, it was not only fish, but other organisms were also discrupted Accordingly, research conducted on the species of fish foound in the river Kenagarian Aur Begalung district of Bayang Pesisir Selatan. This research conducted to determine the species of fish in the river Kenagarian Aur Begalung district of Bayang. This research conducted in August-September 2014 by using descriptive methods, that is observation and sampling from the ground of research. The sampling was based on a diffrerent a river conditions. The samples were obtained in the laboratory indentified of ecology Andalas University. Based on the results of research conducted, it found as many as 12 species of fish namely Accrochordinichtys chamaeleon, Ambassis vachelli, Caranx ignobilis, Glossogobius aureus, Mystus nigriceps, Oreochromis niloticus, Osteochillus hasselti,Osteochillus schlegeli, Oxygaster anomalura, Puntius sarana, Sicyopterus macrostetholepis, and Tor tambra. The factor of physics-the water temperature of water of chemical, currents speed, pH of water in the river Aur Begalung obtained still eligible to fish life.